2015
DOI: 10.1111/iej.12538
|View full text |Cite
|
Sign up to set email alerts
|

Are posts necessary for the restoration of root filled teeth with limited tissue loss? A structured review of laboratory and clinical studies

Abstract: Guidelines for post placement are lacking in respect of the amount of tooth structure, particularly in cases in which ≥50% of coronal structure is preserved. The aim of this review was to provide evidence-based principles for the use of posts in the restoration of root filled teeth with limited tissue loss. A literature search of laboratory and clinical studies published between 2000 and 2014 was conducted in PubMed. Included studies contained at least one study group with root filled teeth restored without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
(60 reference statements)
1
29
0
1
Order By: Relevance
“…Ferrari et al 28 and Creugers et al 25 showed that presence of ferrule and preservation of coronal walls increased survival rates of post-restored teeth. Such findings confirm the importance of preserving tooth structure on the performance of endodontically-treated teeth, 41 which may be even more important than the choice of the core.…”
Section: 39supporting
confidence: 62%
See 1 more Smart Citation
“…Ferrari et al 28 and Creugers et al 25 showed that presence of ferrule and preservation of coronal walls increased survival rates of post-restored teeth. Such findings confirm the importance of preserving tooth structure on the performance of endodontically-treated teeth, 41 which may be even more important than the choice of the core.…”
Section: 39supporting
confidence: 62%
“…In cases of limited tissue loss, post placement does not seem to affect the survival of endodontically-treated teeth. 41 However, when a post is placed, the remaining dental structure influences the performance of root-filled teeth. Ferrari et al 28 and Creugers et al 25 showed that presence of ferrule and preservation of coronal walls increased survival rates of post-restored teeth.…”
Section: 39mentioning
confidence: 99%
“…, Aurelio et al . ), whilst others use more generic terms such as ‘substantial’ or ‘minimal dentine height’ remaining (Creugers et al . , Fokkinga et al .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several suggestions on how to classify the amount of remaining sound coronal tooth structure in root filled teeth. Some authors refer to the percentage of residual tooth structure without defining how this percentage has been measured (Juloski et al 2014, Aurelio et al 2015, whilst others use more generic terms such as 'substantial' or 'minimal dentine height' remaining (Creugers et al 2005, Fokkinga et al 2007, limited loss of coronal tooth structure in teeth with mesial or distal caries with cusp preservation (Mannocci et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By means of in vitro studies, it is possible to standardize and to isolate a variable of interest, elucidating any doubts prior to conducting clinical studies 1 . However, over the past few decades, the validity of some in vitro dental materials studies has been questioned due to the variability in the methodological parameters, the lack of representativeness of the clinical mechanism of failure and the poor correlation with clinical behavior 2,3 .…”
Section: Introductionmentioning
confidence: 99%